Development and application of automatic monitoring equipment for differential deformation of element joint in immersed tunnel - Guo, Hongyan; Yan, Yu; Ding, Hao; Liu, Xinrong; Yang, Men (Frontiers in Physics, 2023)
The reliability of the immersed tunnel element joint is the key to determine whether the immersed tunnel can operate safely. At present, the immersed tunnel monitoring mostly pays attention to the joint opening and closing amount and neglects the differential deformation of the joint. However, the differential deformation is a key parameter for the description of the shear deformation form of GINA waterstop. It is an important index to evaluate the water tightness of the joint from the perspective of the shear resistance and deformation capacity of GINA waterstop. Therefore, it is necessary to conduct supplementary monitoring on the differential deformation of the joint. The existing conventional monitoring technologies and means are difficult to meet the performance index requirements of high precision, low cost, non-contact, automation and intelligence simultaneously. Based on the immersed tunnel of Hong Kong-Zhuhai-Macao Bridge, combined with the operating environment and structural characteristics of the immersed tunnel, this paper introduces a close-range photogrammetry method to monitor the differential deformation of the immersed tunnel element joint, puts forward a comprehensive multi-parameter evaluation and screening algorithm of boundary fitting ellipse based on fitting rate, ellipticity and area difference and a micro-displacement correction algorithm for camera based on three-dimensional calibration object, and develops an automatic monitoring system equipment for differential deformation of immersed tunnel element joint. Upon tests in tunnels, the monitoring equipment is proven in automatic monitoring on differential deformation of immersed tunnel element joints, with effective monitoring range of 0 60m (tunnel axis direction). The effective coverage range of a camera’s fixed focal length is 20m (axial) *5m (transverse), and the actual displacement measurement accuracy is ±0.2mm.This equipment has been successfully applied to the E31 E32 element joint of Hong Kong-Zhuhai-Macao Bridge immersed tunnel，which verifies the effectiveness of the equipment from the perspective of practical engineering application.